Semiotic codes in political propaganda. Analysis of the campaign "The devil spends work" - Castillo, Johana (Quórum Académico, 2022)
This article describes the semiotic codes and subcodes present in the political propaganda "The devil spends work": an animated television series based on the traditional verses of "Florentino and el Diablo", presented in the electoral campaign prior to the Recall Referendum to the President of Venezuela Hugo Chávez on August 15, 2004. The selected units intentionally presented a political discourse with historical and cultural references that delegitimized their opponent (Democratic Coordinator) with simple discursive strategies and that through jokes legitimized Chávez’s speech. The semiotic codes and subcodes were topicalized, related, articulated and synchronized in an audiovisual text that gave the message a favorable meaning to the NO option (officialism) ridiculing the YES option (opposition).